Dualisation of Part-Time Work The Development of Labour Market Insiders and Outsiders - Nicolaisen, Heidi; Kavli, Hanne Cecilie; Steen Jensen, Ragnhild (Policy Press, 2019)
"ePDF and ePUB available Open Access under CC-BY-NC-ND licence. This book brings together leading international authors from a number of fields to provide an up-to-date understanding of part-time work at national, sector, industry and workplace levels. The contributors critically examine part-time employment in different institutional settings across Europe, the USA, Australia and Korea. This analysis serves as a prism to investigate wider trends, particularly in female employment, including the continued increase in part-time work and processes that are increasingly creating dualisation and inequality between 'good' and 'bad' jobs."